Randomized comparison of prophylactic and minimal residual disease-triggered imatinib after allogeneic stem cell transplantation for BCR-ABL1-positive acute lymphoblastic leukemia - Pfeifer, Heike; Wassmann, B.; Bethge, W.; Dengler, Jolanta; Bornhäuser, M.; Stadler, M.; Beelen, D.; Vucinic, V.; Burmeister, T.; Stelljes, M.; Faul, C.; Dreger, Peter; et al. (Leukemia, 2013)
Minimal residual disease (MRD) after allogeneic stem cell transplantation (SCT) for Ph+ acute lymphoblastic leukemia (ALL) is predictive of relapse. Imatinib administration subsequent to SCT may prevent relapse, but the role of scheduling and its impact on outcome are not known. In a prospective, randomized multicenter trial, we compared the tolerability and efficacy of post-transplant imatinib administered either prophylactically (arm A; n=26) or following detection of MRD (arm B; n=29). Prophylactic imatinib significantly reduced the incidence of molecular recurrence after SCT compared with MRD-triggered imatinib (40% vs 69%; P=0.046). Median duration of PCR negativity was 26.5 and 6.8 months, respectively (P=0.065). Five-year survival in both interventional groups was high (80 and 74.5%), despite premature discontinuation of imatinib in the majority of patients because of poor tolerability. Relapse probability was significantly higher in patients who became MRD positive (P=0.017). In conclusion, post-transplant imatinib results in a low relapse rate, durable remissions and excellent long-term outcome in patients with BCR-ABL1-positive ALL irrespective of whether it is given prophylactically or MRD-triggered. Reappearance of BCR-ABL1 transcripts early after SCT or at higher levels identifies a small subset of patients who do not benefit sufficiently from imatinib, and in whom alternative approaches should be explored.